GP123 Altered systemic inflammatory response in paediatric mild traumatic brain injury. (June 2019) - Ryan, Emer; Duff, Eimear; Huggard, Dean; Bates, Mark; Doherty, Derek G; Melo, Ashanty M; Molloy, Eleanor
Abstract : Aims: To evaluate systemic inflammation in TBI by exploration of the inflammasome pathway, a component of the innate immune system that regulates and induces inflammation. We examine the pathway at baseline in TBI compared with healthy control children, and in vitro in response to both LPS stimulation and melatonin therapy. Melatonin has protective effects against NLRP3 inflammasome activation and has therapeutic implications. Methods: Whole blood was sampled from children with TBI (n=10) within 24 hours of injury and compared to healthy age-matched controls (n=8) at baseline, following stimulation with bacterial endotoxin (LPS) (10ng/ml) and melatonin treatment (10 –3 M). Granulocytes were delineated as CD66b+ and FSC, SSC-A. Measurements of mean channel fluorescence (MCF) of CD11b and TLR4 expression on FACS Canto II were recorded and analysed with FloJo software v10. Gene Expression of NLRP3 via rtPCR was recorded in 10 patients and 10 controls at baseline and following LPS and melatonin treatment. Results: Granulocyte CD11b expression was lower in children with TBI compared to controls (p=0.04) Both upregulated CD11b with LPS stimulation. Melatonin significantly decreased this LPS upregulation. There was no significant difference in baseline TLR4 expression between TBI and controls, but LPS upregulation of TLR4 was decreased by melatonin in the TBI cohort. Inflammasome was upregulated via NLRP3 expression in children with TBI compared to controls (p= 0.02). Melatonin significantly decreased LPS-induced upregulation of NLRP3 only in controls. Conclusion: Inflammation is altered in TBI compared to controls with altered responsiveness to melatonin treatment following LPS stimulation. The inflammasome is downregulated in children immediately following TBI. Selective inhibition of systemic inflammation targeting the inflammasome may have a future immunomodulatory role as a target in treating TBI.